Effect of the consumption of a synbiotic diet mousse containing Lactobacillus acidophilus La-5 by individuals with metabolic syndrome: A randomized controlled trial. (February 2018) - Xavier-Santos, Douglas; Lima, Egidio Dorea; Simão, Andréa Name Colado; Bedani, Raquel; Saad, Susana Marta Isay
Highlights: The effect of a synbiotic mousse on metabolic syndrome risk factors was evaluated. No changes observed in the anthropometric measures, heart rate, and blood pressure along the study. Synbiotic and placebo groups showed decreased total cholesterol and HDL-C levels. Both groups had a reduction in IL-1β, IgA, and IgM levels throughout the study. Pro- and prebiotic compounds in mousse did not affect risk factors related to MetS. Abstract: This study aimed to evaluate the impact of a synbiotic diet mousse containing Lactobacillus acidophilus La-5 and the prebiotics inulin and fructooligosaccharides on anthropometric and blood pressure measurements, biochemical, inflammatory, haematological, and immunological parameters of volunteers with metabolic syndrome (MetS). In a randomized, double-blind, placebo-controlled trial, forty-five volunteers with MetS were assigned into two groups, each receiving 40 g/day of: synbiotic diet mousse (SDM) (n = 23) and placebo diet mousse (PDM) without pro- and prebiotics (n = 22). All the evaluated parameters were measured at the beginning and after 8 weeks of intervention. The daily intake of SDM and PDM led to significant reductions of total cholesterol and HDL-cholesterol, as well as of immunoglobulins (A and M), and interleukin-1β in both groups ( p  < .05). These results suggest that the presence of the probiotic and prebiotic ingredients in the diet mousse did not show any additional effects on the parameters evaluated in volunteers with MetS.